2015
DOI: 10.1177/1934578x1501001126
|View full text |Cite
|
Sign up to set email alerts
|

A New Isocyanosesquiterpene from the Nudibranch Phyllidiella pustulosa

Abstract: In the course of our study on the chemical and genetic diversity of the nudibranch Phylidiella pustulosa, we identified a series of isocyanosesquiterpenes. In addition to known sesquiterpenes, we isolated a new molecule 1, the structure of which was elucidated by analyzing NMR and other spectral data. We report the structure and cytotoxicity of compound 1 herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Many other phyllidid species ( P. rosans (P. bourguini) , P. coelestis , P. ocellata , Phyllidia sp, Phyllidiella pustulosa , Phyllidiopsis krempfi , etc.) contain a wide variety of these and other nitrogenated compounds, but these have not been tested for toxicity [ 101 , 102 , 103 , 111 , 114 , 118 , 119 , 120 , 122 , 373 , 374 , 375 , 376 , 377 ].…”
Section: Ecological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many other phyllidid species ( P. rosans (P. bourguini) , P. coelestis , P. ocellata , Phyllidia sp, Phyllidiella pustulosa , Phyllidiopsis krempfi , etc.) contain a wide variety of these and other nitrogenated compounds, but these have not been tested for toxicity [ 101 , 102 , 103 , 111 , 114 , 118 , 119 , 120 , 122 , 373 , 374 , 375 , 376 , 377 ].…”
Section: Ecological Activitymentioning
confidence: 99%
“…Since the isolation of 9- iso cyanopupukeanane ( 21 ) from Phillidia varicosa [ 106 ], phyllidids have been shown to be chemically rich, presenting many nitrogenous mono-, bi- and tri-cyclic sesquiterpenes, usually traced back to their sponge prey [ 1 , 4 , 22 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 110 , 111 , 114 , 116 , 118 , 119 , 120 , 122 , 374 , 375 , 376 , 377 , 437 ]. Some of these compounds are potent antifouling agents, effective against barnacle larvae, such as the bisabolene 3- iso cyanotheonellin ( 161 ) of P. varicosa from Sri Lanka, and a sesquiterpene isonitrile from the Japanese Phyllidiella pustulosa [ 102 , 103 , 114 , 115 , 116 , 437 ].…”
Section: Ecological Activitymentioning
confidence: 99%
“…Sea slugs of the genus Phyllidiella and Phyllidia are prolific in the South China Sea. They are well known for their ability to ingest toxic nitrogenous sesquiterpenoids from their diets, and use either these metabolites themselves or their biosynthetically transformed derivatives as a weapon for chemical defense [1,2,3,4,5,6,7]. An intriguing ecological study showed that when sea slugs are under attack, they release a lot of mucus containing these nitrogenous metabolites to poison their enemies [8].…”
Section: Introductionmentioning
confidence: 99%
“…229 Subsequent studies have found a number of related nitrogenous mono-, bi-and tricyclic sesquiterpenes from Phyllidia sp., 230 P. varicosa, 231,232 P. ocellata, 232-234 P. coelestis, 235 and P. pustulosa. 231,232,236,237 Phyllidia pustulosa has been reclassied as Phyllidiella pustulosa 413 so unsurprisingly, several studies of the animal reported as Phyllidiella pustulosa also yielded nitrogenous sesquiterpenes, [238][239][240][241][242] although one additionally yielded nitrogenous diterpenes, 240 which had also been isolated previously from a sponge. 240 Phyllidiopsis kremp also yielded nitrogenous sesquiterpenes and a sesquiterpene peroxide.…”
Section: Phyllidioideamentioning
confidence: 99%